The Ideology of President Joko Widodo through His Inauguration Speech - Ayang Winda Sri Widianingsih (Ma'soem University, 2021)
This study focuses on analyzing a presidential speech, Joko Widodo in his inauguration on October, 2014. In order to gain clear explanation about the transitivity and its modality also the ideology of Joko Widodo, Critical Discourse Analysis through functional linguistic analysis is employed. This metafunction analysis is based on Halliday & Matthiessen (2004) and Fairclough (1995). It is found that there are three processes used mainly by the speaker such material, mental and relational. The material process is utilized to state what happens, many linking verbs to state what is or should be and mental process to state what speaker thinks or feels about issue. Meanwhile, modality alludes to the point of view or conclusion of the speaker on the reality of a suggestion communicated in a sentence. Jointly, it expands their demeanor to a case or occasion that's characterized by a statement. Social cognition as the ideology of Joko Widodo shows the widespread use of non-public pronouns. Pronouns I and we are widely used in speech than others. The findings of this study may contribute to expanding the critical thinking skills of readers in language understanding and production.